Pemilihan Fungsi Sosial dan Fungsi Rohani Bagi Korban Penyalahgunaan Narkoba di Yayasan Amanat Agung Medan - Malida Putri; Bryan Egianta Tarigan (Yayasan Literasi Sains Indonesia, 2023)
Recovery is a process that a drug addict must go through if he wants to be completely cured of his addiction. Recovery does not mean just stopping using (drugs), recovery must be understood as the creation of a newlifestyle, thus it will be easier for someone to decide not to use (drugs) again. In recovery there are three things that must be considered, namely avoiding high-risk situations, learning how to relax, and telling the truth. Recovery demands total honesty, that is, if you want to recover, you have to be one hundred percent honest with the people who support you, such as family, doctors, therapists, etc. If you can't be honest with them then the recovery won't go well. Being totally honest means not givinghis addictive nature a place to hide. If you lie, it means you have opened the door for relapse. An opportunity to change life can be seen as an opportunity to change life. Changing lives is what makes recovery difficult but also profitable. Recovery is difficult because a person has to change his or her life, and all changes are difficult, even if it turns out to be good. Recovery is beneficial because a person gets the opportunity to change his life. If we take the opportunity to change, then we will look back and reflect on our addiction as the one good thing that ever happened in life. In recovery, people often describe themselves as grateful addicts. Why should someone be grateful to have experienced an addiction because starting from that addiction they are then helped to find the peace and serenity that many people seek. Recovery (recovery) can encourage a person to change his life